Synthesis and Crystal Structure of Diethyl Tosyloxybenzylphosphonate - Kong, Du-Lin; Li, Guo-Zhu; Liu, Ren-Die (Asian Journal of Chemistry, 2014)
Diethyl tosyloxybenzylphosphonate was synthesized by the reaction of hydroxybenzylphosphonate with p-toluenesulfonyl chloride characterized by NMR spectroscopy, elemental analyses and X-ray single-crystal diffraction. The possessing parameters: m.f. C18H23O6PS, monoclinic, P2(1)/n, a = 8.1087(9) Å, b = 20.215(2) Å, c = 12.5201(12)Å, a = 90º, b = 98.7380(10)º, g = 90º, V = 2028.5(4) Å3, Z = 4, Mr = 398.39, Dc = 1.305 g/cm3, μ = 0.268 mm-1, F(000) = 840, T = 298(2) K, R1 = 0.0462, wR2 = 0.1076 for 3579 observed reflections with I >2s(I).